Analisis Kemampuan Pemecahan Masalah Matematis Siswa pada Materi Persamaan Kuadrat - Farel Gusta Juyan Putra; Eline Yanty Putri Nasution (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Mathematical problem-solving ability is an essential competency in mathematics learning because it enables students to analyze, plan, and solve mathematical problems systematically. However, many students still encounter difficulties in solving algebra problems, particularly in evaluating the correctness of their solutions. Therefore, this study aimed to analyze the profile of students’ mathematical problem-solving ability in algebra based on Polya’s problem-solving stages. This study employed a descriptive qualitative research design. The population consisted of all SMA Negeri 2 Kerinci students, totaling 21 tenth-grade students as the research sample that was selected using a purposive sampling technique. Data were collected through a mathematical problem-solving test administered to all students, after which four students representing the categories of very good, good, fair, and poor were selected purposively for in-depth analysis. The instrument was tested for validity, reliability, item difficulty, discrimination index, and item correlation using SPSS. The results indicated that 9.52% of students were categorized as very good, 28.57% as good, 52.38% as fair, and 9.52% as poor. Based on Polya’s stages, students achieved 71.43% in understanding the problem, 85.71% in devising a plan, 66.67% in carrying out the plan, and 4.76% in looking back. The findings reveal that most students were able to understand problems, devise solution strategies, and carry out solution plans, whereas the looking-back stage remained the weakest aspect of their mathematical problem-solving profile. These findings imply that mathematics instruction should emphasize not only obtaining correct answers but also developing students’ habits of solving problems systematically and verifying their solutions.